Efektivitas Terapi Pijat Es Untuk Mengurangi Nyeri Pada Pasien Penyakit Ginjal Kronis - Muharani Syaftriani, Afina; Haryanti Butar-butar, Maria; Mahraniy, Mahraniy; Darayani Purba, Widya; Fadillah, Fitriani; Payung, Riduan (JINTAN: Jurnal Ilmu Keperawatan, 2025)
Chronic kidney disease (CKD) is a progressive medical situation that leads to decrease within renal operation, an increase in ureum levels, and disruptions in the body's metabolic, fluid, and electrolyte balance. Approximately 10% of the global population is affected by CKD, with over 1.5 million individuals undergoing hemodialysis (HD). The objective Belonging to this particular research represents in order to evaluate the efficacy of ice massage therapy in alleviating pain in CKD patients receiving treatment at Rasyida Hospital Medan. The research employed a semi-experimental framework, along with 119 CKD patients, and 15 Participants were chosen employing intentional selection. The chi-square numerical examination results indicated a p-value of less than 0.05 before the application of ice massage therapy to reduce pain, and after therapy, the p-value decreased to 0.001. Founded upon these particular results, the study concluded that ice massage therapy is effective in reducing pain in CKD patients at Rasyida Hospital Medan. Consequently, it is recommended that hospitals consider incorporating ice massage Treatment in the role of one approach to alleviate pain in CKD patients.